2008
DOI: 10.1152/ajplung.00210.2007
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of resident alveolar macrophages does not prevent Fas-mediated lung injury in mice

Abstract: Activation of the Fas/Fas ligand (FasL) system in the lungs results in a form of injury characterized by alveolar epithelial apoptosis and neutrophilic inflammation. Studies in vitro show that Fas activation induces apoptosis in alveolar epithelial cells and cytokine production in alveolar macrophages. The main goal of this study was to determine the contribution of alveolar macrophages to Fas-induced lung inflammation in mice, by depleting alveolar macrophages using clodronate-containing liposomes. Liposomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…In keeping with previous studies in rodents (36,37), prior compartmental depletion of resident AMs did not reduce experimental pulmonary inflammation ( Figure E3). …”
Section: Lc Delivered Locally To the Lung Depletes Ams But Does Not Asupporting
confidence: 91%
“…In keeping with previous studies in rodents (36,37), prior compartmental depletion of resident AMs did not reduce experimental pulmonary inflammation ( Figure E3). …”
Section: Lc Delivered Locally To the Lung Depletes Ams But Does Not Asupporting
confidence: 91%
“…Surface expression of CD40 on pulmonary dendritic cells has been reported to be increased by smoke inhalation in mice (11). However, Matute et al (4,25) reported that, in acute lung injury, Fas directly affects alveolar cells, not via myeloid cells such as alveolar macrophages. Indeed, we did not detect increased numbers of apoptotic immune cells in lungs of our mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Fas-induced lung injury requires Fas-expression on nonmyeloid cells of the lung [120], emphasizing the role of lung epithelial cell dependent mediator release, and apoptosis. In the absence of resident AM, Fasinduced lung damage was worsened [21], displayed by significantly increased BAL protein concentration and lung histology. Furthermore, depletion of AM increased lung damage and inflammation following non-lethal unilateral lung contusion in mice [109].…”
Section: Apoptosismentioning
confidence: 99%
“…Among the discussed signal transduction pathways nuclear factor-kappa B (NF-B) [145], extracellular signal regulated kinase 1/2 (ERK 1/2), and mitogen-activated protein kinase p38 (p38 MAPK) [141] have been suggested to be involved. The observation of a marked inflammatory response in the absence of alveolar macrophages [21,152] is important because it suggests that other cell types in the lung can promote inflammation in response to Fas. An important role of neutrophils in Fas-induced inflammation has been suggested and was part of this study.…”
Section: Inflammationmentioning
confidence: 99%